(untitled) (Modern education and development, 2024)
The effect of temperature on the current-voltage (I-V) characteristics of silicon-based semiconductor materials is a critical factor influencing their performance in electronic applications. This study explores the temperature-dependent behavior of the I-V curve, highlighting key phenomena such as carrier mobility, bandgap narrowing, and thermal generation of charge carriers. Experimental data and theoretical analysis are combined to provide insights into optimizing semiconductor devices for various temperature ranges.